Ebola in great apes – current knowledge, possibilities for vaccination, and implications for conservation and human health. (5th December 2016) - Leendertz, Siv Aina J.; Wich, Serge A.; Ancrenaz, Marc; Bergl, Richard A.; Gonder, Mary K.; Humle, Tatyana; Leendertz, Fabian H.
Abstract: Ebola virus disease (EVD) is a threat to human health and to the survival of African great apes. The disease has led to major population declines in chimpanzees Pan troglodytes and gorillas Gorilla gorilla, and infected great apes play an important role as sources of human EVD outbreaks. The threat posed by EVD raises the question whether vaccination of wild apes is an effective strategy to reduce the occurrence and impact of this disease. We review the current knowledge about EVD in great apes and document the link between outbreaks in apes and in humans, mainly via bushmeat consumption. We discuss the need for control strategies, such as vaccination, and describe aspects of primate behaviour, virus biology, vaccine composition, and vaccination principles that need to be considered when making management decisions about great ape vaccination. Finally, we identify gaps in the understanding of Ebola ecology and highlight surveillance and research that can aid the survival of great apes and reduce human exposure to Ebola virus. The severe impact of EVD indicates the need for efficient monitoring and, ultimately, control of Ebola. However, the unknown reservoir and unpredictable emergence of Ebola, the elusive nature of great apes, and the lack of licensed and suitable vaccines represent major hurdles for such control. Public education about zoonotic diseases and monitoring of great ape health are both important strategies. Experts should also discuss the feasibility of developing safe vaccines that can be delivered efficiently to large populations of elusive wild apes in their natural remote habitats. This review provides a platform for further interdisciplinary discussions, so that management plans can be discussed and adjusted according to possible future changes in the development, availability and cost of vaccines, the status of EVD, knowledge about Ebola ecology, and opinion on wildlife vaccination.